2000
DOI: 10.2307/177395
|View full text |Cite
|
Sign up to set email alerts
|

Do Nocturnal Ectotherms Thermoregulate? A Study of the Temperate Gecko Christinus marmoratus

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.Abstract. Current paradigms relating to reptilian temperature regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
102
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(105 citation statements)
references
References 48 publications
1
102
0
2
Order By: Relevance
“…In rocky habitats, reptiles often thermoregulate inside crevices formed by overlying rocks located in sun-exposed locations (Huey et al 1989, Kearney andPredavec 2000). These microhabitats provide access to the warmest temperatures available (Webb and Shine 1998a), but are limited by the openness of the forest canopy (Pringle et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In rocky habitats, reptiles often thermoregulate inside crevices formed by overlying rocks located in sun-exposed locations (Huey et al 1989, Kearney andPredavec 2000). These microhabitats provide access to the warmest temperatures available (Webb and Shine 1998a), but are limited by the openness of the forest canopy (Pringle et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Thermoregulatory opportunities are generally more limited for nocturnal animals than for diurnal animals (Huey et al 1989;Kearney and Predavec 2000). However, nocturnal lizards do thermoregulate (Huey et al 1989;Kearney and Predavec 2000;Kearney 2001Kearney , 2002.…”
mentioning
confidence: 99%
“…Thus, diurnal thermoregulation for nocturnal ectotherms is limited to retreat site selection and their ability to exploit thermal conditions provided by their diurnal retreat (Kearney and Predavec 2000). This was first shown by Huey et al (1989), which demonstrated that garter snakes used basalt rocks nonrandomly based on their thickness, allowing snakes to maintain their body temperatures around their thermal optimum but avoid lethal temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In summer, rocks become too hot for many saxicolous animals on sandstone outcrops, causing the animals to abandon the outcrops to more thermally suitable retreats like tree hollows or deep rock crevices (e.g., broadheaded snakes: Shine 1997, Webb andShine 1998;marbled geckos: Kearney 2002). Animals that continue using exfoliated rocks throughout summer when the maximum temperatures are at their highest could mitigate the probability of encountering these thermal extremes either by behavioral retreat site selection (Kearney and Predavec 2000) or through having high thermal tolerances.…”
Section: Introductionmentioning
confidence: 99%